1994
DOI: 10.17520/biods.1994048
|View full text |Cite
|
Sign up to set email alerts
|

Ultradry Seed Storage: Improved Strategy and Technology for Germplasm Conservation

Abstract: Mammals are key indicators for biodiversity conservation and management due to their high diversity, wide distribution range, and sensitivity to habitat changes. Recently launched by the Chinese Academy of Sciences, the Mammal Diversity Monitoring Network of Sino BON (Sino BON-Mammal) is a key member of the Biodiversity Monitoring Networks of Sino BON for the monitoring and inventory of terrestrial mammal resources in China. Firstly, this paper reviews several major advances in terrestrial mammal diversity obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Cromarty et al (1982) recommended seed drying at low temperature (15 0 C) and low relative humidity (15%) for safe storage. Guanfhua (1994) reported that the ultradrying of seeds improves seed storability. Ultra dry (2.0 to 3.7% moisture content) seeds preserve viability better than dry (5.5 to 6.8% moisture content) seeds at 20 0 C (Ellis et al, 1996).…”
Section: Effect Of Storage Seed Moisture Levels On Seed Qualitymentioning
confidence: 99%
“…Cromarty et al (1982) recommended seed drying at low temperature (15 0 C) and low relative humidity (15%) for safe storage. Guanfhua (1994) reported that the ultradrying of seeds improves seed storability. Ultra dry (2.0 to 3.7% moisture content) seeds preserve viability better than dry (5.5 to 6.8% moisture content) seeds at 20 0 C (Ellis et al, 1996).…”
Section: Effect Of Storage Seed Moisture Levels On Seed Qualitymentioning
confidence: 99%
“…Many studies have indicated that seed aging is associated with antioxidant enzymes, MDA, and amylase activity, which is consistent with studies on E. villosa seeds. Zheng [59] showed that the AMS activity of poplar seeds tended to decrease to different degrees during storage. Hao [60] and Chang et al [61] showed that the POD activity of Pinus oleifera seeds decreased significantly, while the MDA content increased significantly with increasing storage time, and the SOD and CAT activities of sand onion seeds increased and then decreased with increasing storage time and were positively correlated with their germination indexes.…”
Section: Discussionmentioning
confidence: 99%